Anomalous pH‐Dependent Nanofluidic Salinity Gradient Power. Issue 48 (24th October 2017) - Yeh, Li‐Hsien; Chen, Fu; Chiou, Yu‐Ting; Su, Yen‐Shao
Abstract: Previous studies on nanofluidic salinity gradient power (NSGP), where energy associated with the salinity gradient can be harvested with ion‐selective nanopores, all suggest that nanofluidic devices having higher surface charge density should have higher performance, including osmotic power and conversion efficiency. In this manuscript, this viewpoint is challenged and anomalous counterintuitive pH‐dependent NSGP behaviors are reported. For example, with equal pH deviation from its isoelectric point (IEP), the nanopore at pH < IEP is shown to have smaller surface charge density but remarkably higher NSGP performance than that at pH > IEP. Moreover, for sufficiently low pH, the NSGP performance decreases with lowering pH (increasing nanopore charge density). As a result, a maximum osmotic power density as high as 5.85 kW m −2 can be generated along with a conversion efficiency of 26.3% achieved for a single alumina nanopore at pH 3.5 under a 1000‐fold concentration ratio. Using the rigorous model with considering the surface equilibrium reactions on the pore wall, it is proved that these counterintuitive surface‐charge‐dependent NSGP behaviors result from the pH‐dependent ion concentration polarization effect, which yields the degradation in effective concentration ratio across the nanopore. These findings provide significant insight for the design of next‐generation, high‐performance NSGP devices. Abstract : A pH‐regulated nanopore, having smaller surface charge density but remarkably higher performance of nanofluidic salinity gradient power (NSGP), is demonstrated for the first time. The counterintuitive surface‐charge‐dependent NSGP behavior is also shown resulting from the pH‐dependent ion concentration polarization effect, which yields degradation in an effective concentration ratio across a nanopore.